2015
DOI: 10.1021/jp5122239
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interactions of Gelatin Nanoparticles with the Major Lipids of Model Lung Surfactant: Changes in the Lateral Membrane Organization

Abstract: There has been an increasing interest in the potential of nanomedicine, particularly in the use of nanoparticles between 10 nm and 1 μm in diameter as drug delivery vehicles. For pulmonary drug delivery, it is important to understand the effect of polymeric nanoparticles on the lung surfactant in order to optimize the carriers by reducing their potential toxicological effects. This work presents a biophysical study of the impact of gelatin nanoparticles on packing and lateral organization of simple and complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…Among the many air pollutants, PM2.5 is the most well-known one, which refers to a kind of particulate matter with a particle size of 2.5 μm or less. Due to the small particle size, PM2.5 is easily inhaled and causes respiratory diseases. Since the discovery of human alveolar surface covered with a pulmonary surfactant (PS) monolayer, which is composed of phospholipids, neutral lipids, and specific proteins, by Pattle and Clements in the 1950s, the PS monolayer is regarded as the first barrier where external nanoparticles enter the body through respiration, and it inevitably interacts with the inhaled nanoparticles. The Langmuir–Blodgett monolayer technique on the air–water surface is a classical two-dimensional surface chemistry method, which is widely applied for the simulation of cell membrane , and pulmonary surfactant (PS) monolayer in vitro. The mixed monolayer composed of PC and PG in the ratio of 4:1 was widely adopted to mimic the real PS monolayer according to the compositional analysis of mammalian lung surfactant extracts. Meanwhile, in the technical means of exploring the interaction between substances and biomembranes, molecular dynamics (MD) simulation has the ability to efficiently obtain the behavior and distribution of substances in cell membranes at the molecular detail, so it is widely adopted to study the interactions between lipid membranes and drugs, , drug carriers, and nanoparticles. , …”
Section: Introductionmentioning
confidence: 99%
“…Among the many air pollutants, PM2.5 is the most well-known one, which refers to a kind of particulate matter with a particle size of 2.5 μm or less. Due to the small particle size, PM2.5 is easily inhaled and causes respiratory diseases. Since the discovery of human alveolar surface covered with a pulmonary surfactant (PS) monolayer, which is composed of phospholipids, neutral lipids, and specific proteins, by Pattle and Clements in the 1950s, the PS monolayer is regarded as the first barrier where external nanoparticles enter the body through respiration, and it inevitably interacts with the inhaled nanoparticles. The Langmuir–Blodgett monolayer technique on the air–water surface is a classical two-dimensional surface chemistry method, which is widely applied for the simulation of cell membrane , and pulmonary surfactant (PS) monolayer in vitro. The mixed monolayer composed of PC and PG in the ratio of 4:1 was widely adopted to mimic the real PS monolayer according to the compositional analysis of mammalian lung surfactant extracts. Meanwhile, in the technical means of exploring the interaction between substances and biomembranes, molecular dynamics (MD) simulation has the ability to efficiently obtain the behavior and distribution of substances in cell membranes at the molecular detail, so it is widely adopted to study the interactions between lipid membranes and drugs, , drug carriers, and nanoparticles. , …”
Section: Introductionmentioning
confidence: 99%
“…Naturally, factors inhibiting the surface tension-lowering properties of the interfacial-lining material have severe consequences . As an example, polymer nanoparticles provoked biophysical dysfunctions of lung surfactant through a depletion of individual surfactant constituents (e.g., surfactant-associated proteins), due to binding to the colloidal surface. Interestingly, surface modifications of polymer nanoparticles (e.g., by coating with poly­(ethylene glycol)-containing copolymers) attenuated bioadverse events in silico and during relevant in vitro experimentation . However, no information is available describing the specific characteristics of the steric surface shielding (e.g., coating layer thickness and density) necessary to overcome unwanted polymer nanoparticle–lung surfactant interactions.…”
Section: Introductionmentioning
confidence: 99%
“…If the reverse contrast observed herein from the initial stages of phase separation and condensed domain formation was attributable to multilayer formation, the compression isotherm should be shifted to significantly smaller molecular areas. On the other hand, Daear et al 29 reported an inversion of contrast at high surface pressures when cospreading cationic gelatin nanoparticles within a dipalmitoylphosphatidylglycerol (DPPG) monolayer. If the cationic nanophytoglycogen embeds in the POPG-rich fluid phase, a large film expansion and shift in the isotherm to greater molecular areas should be observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the alveoli, the nanoparticles interact with the pulmonary (or lung) surfactant, a lipid–protein mixture that lines the alveolar air/fluid interface and serves as the primary barrier to uptake . The main role of the pulmonary surfactant is to prevent alveolar collapse at the end of expiration and reduce the work of breathing. , The physicochemical characteristics of the nanoparticles (i.e., surface charge, hydrophobicity, size) dictate their interactions with the pulmonary surfactant. , These interactions can alter the surface-tension-lowering capability of the surfactant membrane, its phase structure, reservoir formation, and mechanical properties, all critical to breathing. Hydrophobic nanoparticles are known to irreversibly embed within the monolayer membrane, while hydrophilic ones are more likely to translocate across the monolayer to reach the lung lining fluid. ,, Charged nanoparticles are of interest for the electrostatic binding of biomolecules (e.g., oligonucleotides, peptides, viruses, small molecule therapeutics) to their surface. …”
Section: Introductionmentioning
confidence: 99%